ETIKA KOMUNIKASI DALAM PERGAULAN REMAJA DI KAMPUNG PASAR PAGI, DESA BULUH MANIS, KABUPATEN BENGKALIS - Nilam Ervika Sari (Jurnal Komunikasi, 2023)
In communicating, you must know how so that the information to be conveyed is well received, not offensive and can be understood by the listener. Communication activities can be well established if the communicators are able to respect each other and uphold ethics in communication. The purpose of this research is to explain what are the factors and forms of adolescent communication ethics and how are the real conditions of adolescent association in Pasar Pagi Village, Buluh Manis Village, Bengkalis Regency. This study uses a qualitative method with a descriptive approach. By using data collection techniques through interviews, observation and documentation. The results of this study indicate that adolescents in Pasar Pagi Village, Buluh Manis Village, Bengkalis Regency: (1). The social conditions of adolescents are basically good for their teenagers. Teenagers have applied communication ethics to their parents and the surrounding community. However, the condition of the association of adolescents within the scope of peers, has not yet applied the communication ethics that these adolescents should do. (2). Factors that influence the formation of adolescent communication ethics are the environtment consisting of family and school, habits, foreign culture, organization and social media. (3). Forms of adolescent communication ethics such as maintaining speech, courtesy, mutual respect and respect and accepting differences when communicating, both to parents and the community environment have been applied by adolescents. However, teenagers still use harsh or dirty words when communicating with friends in their relationships